2016
DOI: 10.1007/s00520-016-3321-0
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of sarcopenia in small-cell lung cancer patients by routine chest CT

Abstract: Chest CT-determined L1MI is highly correlated with L3MI in SCLC patients. L1MI, as determined by chest CT, could be used to determine the presence of sarcopenia with suggested cutoffs of 46 cm(2)/m(2) for men and 29 cm(2)/m(2) for women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
60
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(67 citation statements)
references
References 15 publications
4
60
3
Order By: Relevance
“…However, L3 vertebrae is not included in several CT examination protocols, such as chest, pelvis or head and neck CT examinations. Some investigators have assessed alternative measurements for the detection of sarcopenia in patients with chest-only CT or pelvis-only CT examinations [13][14][15][16][17]. Swartz et al [18] compared SMA at L3 level (L3MA) and paravertebral muscle area at the third cervical vertebrae level (C3MA) in 103 subjects (51 trauma patients and 52 patients with malignancy) and they have reported that C3MA may be an alternative to L3MA in head and neck CT examinations.…”
Section: Introductionmentioning
confidence: 99%
“…However, L3 vertebrae is not included in several CT examination protocols, such as chest, pelvis or head and neck CT examinations. Some investigators have assessed alternative measurements for the detection of sarcopenia in patients with chest-only CT or pelvis-only CT examinations [13][14][15][16][17]. Swartz et al [18] compared SMA at L3 level (L3MA) and paravertebral muscle area at the third cervical vertebrae level (C3MA) in 103 subjects (51 trauma patients and 52 patients with malignancy) and they have reported that C3MA may be an alternative to L3MA in head and neck CT examinations.…”
Section: Introductionmentioning
confidence: 99%
“…2 Therefore, various studies have attempted to solve this dilemma by conducting CT scans at different vertebra levels (T4, L1) for SMM estimates in NSCLC patients. 5,6,21,22 Although good results have been achieved, the applications were not so extensive. Herein, an accurate and reproducible classifier was constructed through the integration of a large panel of skeletal muscle CT radiomic features and high efficiency lightGBM model, to differentiate NSCLC patients with sarcopenia from those without sarcopenia, achieving high accuracy and AUC were recorded as 0.900 and 0.889 in optimal lightGBM mode.…”
Section: Discussionmentioning
confidence: 99%
“…66 Several smaller studies have used chest, spine, or neck CTs. [67][68][69][70] Depending on the CT chosen, various muscles and muscle groups have been measured. On abdominal CTs, the region of interest (ROI) used to measure sarcopenia may include the psoas muscles, the paraspinous muscles, and all visualized abdominal muscles (►Figs.…”
Section: Technical Considerationsmentioning
confidence: 99%